1989
DOI: 10.1128/aac.33.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of trospectomycin (U-63366F) and initial evaluations of disk diffusion susceptibility tests

Abstract: The in vitro activities of trospectomycin sulfate were compared with those of spectinomycin against 632 aerobic microorganisms, including 66 Neisseria gonorrhoeae isolates. Against species other than gram-negative bacilli, trospectomycin was about 4-to 16-fold more active than spectinomycin. For disk diffusion tests, a 30-,ug disk is recommended, with tentative zone size breakpoints of '13 mm for resistance (MIC, .64 jig/mi) and .17 mm for susceptibility (MIC, <16 ,ug/ml).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 6 publications
(6 reference statements)
1
7
0
2
Order By: Relevance
“…Um exemplo é o que foi observado em relação ao novo aminociclitol testado, a trospectomicina. Essa droga, o mais potente derivado da espectinomicina, é inativada pelas mesmas enzimas que destroem a estreptomicina e a gentamicina e, portanto, o resultado obtido in vitro (94% de sensibilidade) deve representar falsa sensibilidade 10 . Cloranfenicol e tetraciclina são antimicrobianos para os quais é comum observar-se sensibilidade dos enterococos, mesmo para cepas resistentes a todos os outros antimicrobianos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Um exemplo é o que foi observado em relação ao novo aminociclitol testado, a trospectomicina. Essa droga, o mais potente derivado da espectinomicina, é inativada pelas mesmas enzimas que destroem a estreptomicina e a gentamicina e, portanto, o resultado obtido in vitro (94% de sensibilidade) deve representar falsa sensibilidade 10 . Cloranfenicol e tetraciclina são antimicrobianos para os quais é comum observar-se sensibilidade dos enterococos, mesmo para cepas resistentes a todos os outros antimicrobianos.…”
Section: Discussionunclassified
“…Todos os 87 isolados foram também testados contra dez drogas alternativas potencialmente úteis no tratamento de infecções enterocócicas. As drogas avaliadas foram: ciprofloxacina, clinafloxacina 9 , esparfloxacina, doxiciclina, eritromicina, espectinomicina, trospectomicina 10 , cloranfenicol, trimetoprim-sulfametoxazol e novobiocina. Essas drogas foram avaliadas pelas técnicas de E test e/ou difusão em disco.…”
unclassified
“…During the late 1980s, there were many attempts to make spectinomycin variants for treatment of bacterial infections (39,40), but none of these drugs are in clinical use.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…The following MIC ranges are proposed for the NCCLS HTM method QC guidelines (percent of results in proposed range): cefdinir, 0.5 to 4 p.g/ml (100%); cefepime, 0.5 to 2 ,ug/ml (100%); cefetamet, 0.5 to 2 ,ug/ml (97.3%); cefpirome, 0.25 to 1 ,ug/ml (100%); ceftibuten, 0.25 to 1 p.g/ml (100%); fleroxacin, 0.03 to 0.12 ,ug/ml (100%); temafloxacin, 0.008 to 0.03 ,ug/ml (100%); clarithromycin, 4 to 16 ,ug/ml (100%); RP59500, 4 to 16 pg/ml (100%); trospectomycin, 0.5 to 2 p.g/ml (100%). The 10 new and investigational compounds evaluated in this study have all been shown to have significant activity against H. influenzae (1,2,(4)(5)(6)(7)(8)(9)(10)16). The MIC QC data summarized should expand the number of drugs which can be reliably tested in HTM broth against Haemophilus spp.…”
mentioning
confidence: 93%
“…To expand the number of therapeutic agents that can be tested against Haemophilus spp. isolates, we report MIC quality control (QC) guidelines for 10 drugs having significant activity (1,2,(4)(5)(6)(7)(8)(9)(10)16).…”
mentioning
confidence: 99%